PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN DUNKIN’ DONUTS MANADO TOWN SQUARE - Putri Gianny Erdipriwiranti; Paulus Adrian Pangemanan; Grace Adonia Josefina Rumagit (Sam Ratulangi University, 2019)
This study aims to analyze how influential the brand image, price, and product quality are on consumer loyalty at Dunkin’ Donuts Manado Town Square. This research was conducted for 1 month, starting from April to May 2019. Primary data was obtained from 96 respondents who werecollected through filling out the prepared questionnaire in advance. Sample selection is done using accidental sampling method. Secondary data was obtained through information from the Dunkin' Donuts company, from the internet through google search and google scholar to get articles, journals and theses related to the topic of research on consumer loyalty. The analysis used is multiple linear regression analysis. The results show that brand image, price, and product quality together influence consumer loyalty. Brand image, price, and product quality individually have a positive and significant effect on consumer loyalty. Brand image, price, and product quality have an effect of 47.9 percent on consumer loyalty, and the remaining 52.1 percent is influenced by other factors.*eprm*